Differential invariants of the Euclidian algebra - Egorchenko, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
Functional bases of second-order differential invariants of a Euclidean algebra and a conformal algebra are found for a set of scalar functions depending on n variables.